Quality Improvement Techniques for Recycled Concrete Aggregate: A review - Shaban, Wafaa Mohamed; Yang, Jian; Su, Haolin; Mo, Kim Hung; Li, Lijuan; Xie, Jianhe (Journal of Advanced Concrete Technology, 2019)
The main problem in using recycled concrete aggregate (RCA) as a construction material is due to the weak adhered mortar which usually has higher porosity and water absorption. It also has lower strength compared to natural aggregate (NA), and it often forms weak interfacial transition zones in the recycled aggregate concrete (RAC). These weak zones lead to negative effects on the mechanical properties and durability performance of RAC. In order to utilize RCA in more effectively as aggregate in concrete, it is necessary to improve the quality and enhance the properties of the attached weak mortar. This paper reviews different treatment methods of RCA based on the published research, and systematically analyses the strengths and weaknesses as well as the applicability and limitations of each method. The advantages and disadvantages of each treatment method, in terms of their technical feasibility, efficiency, economic and environmental impacts, are also discussed, in view of facilitating the selection of the most suitable treatment method for RCA. Although most techniques have been examined and trialed under laboratory conditions, further investigations are required to determine the most effective approach for treating RCA, with consideration not only given to the laboratory scale, but also on a commercial production scale.